USING THE STIMULER AI APP TO IMPROVE STUDENTS' SPEAKING SKILLS IN CLASS XI IPS AT MA DDI SONI - Nahdawati Nahdawati; Sitti Hawaena (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2025)
This research examines the profile of student interest, learning obstacles, and student perceptions of the English language learning process at MA DDI Soni. Using a qualitative descriptive approach through a questionnaire instrument, the study evaluates aspects of motivation, linguistic constraints, and the condition of the school environment. The results indicate that although students possess a very high level of future awareness and an ambition to speak fluently, the actual practice of using English in daily life remains classified as low.The primary obstacles identified include vocabulary limitations, mastery of grammar, and psychological barriers such as the fear of making mistakes. However, the support from the school environment, including classroom comfort and learning facilities, is considered adequate in supporting learning motivation. This study highlights the need for a balance between interactive, creative teaching methods and clarity in material explanation to minimize students' learning obstacles.